2012
DOI: 10.1021/sc300063f
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Biochar Water-Extractable Substances on Environmental Sustainability

Abstract: Application of biochar as a soil amendment could be a significant approach for carbon sequestration to possibly control climate change for energy and environmental sustainability. However, more studies are needed in a number of research areas, including the development of clean biochar materials free of any harmful substances, before this approach could be implemented at a global scale. In this study, biochar water-extractable substances were tested for their potential harmful effects on the growth of aquatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 23 publications
2
77
1
1
Order By: Relevance
“…An inhibitory effect of biochar on microorganisms has been observed by others (Dempster et al, 2012) and attributed to water-soluble, low molecular-weight (<500 Da) organic species (Smith et al, 2012), volatile organic compounds , or ethylene (Spokas et al, 2010) released from the biochar. Biochar additions have also been shown to alter the composition of soil bacterial populations, increasing those of families involved with reduction of NO 3 to NH 4 , N 2 fixation, and denitrification but decreasing those involved in nitrification of NH 4 to NO 2 Khodadad et al, 2011;Lehmann et al, 2011;Ducey et al, 2013).…”
Section: Mechanism By Which Biochar Effects Soil Processesmentioning
confidence: 92%
“…An inhibitory effect of biochar on microorganisms has been observed by others (Dempster et al, 2012) and attributed to water-soluble, low molecular-weight (<500 Da) organic species (Smith et al, 2012), volatile organic compounds , or ethylene (Spokas et al, 2010) released from the biochar. Biochar additions have also been shown to alter the composition of soil bacterial populations, increasing those of families involved with reduction of NO 3 to NH 4 , N 2 fixation, and denitrification but decreasing those involved in nitrification of NH 4 to NO 2 Khodadad et al, 2011;Lehmann et al, 2011;Ducey et al, 2013).…”
Section: Mechanism By Which Biochar Effects Soil Processesmentioning
confidence: 92%
“…In fact, the microorganisms can utilize a number of labile biochar constituents as an energy source [22]. While some biochar associated labile components have biocidal activity [54], which may increase its stability against biotic decomposition. For instance, previous studies have shown that the inhibitory component of deleterious some biochars is likely to be low molecular weight organic acids and phenols [55,56].…”
Section: 2 Bchypy Fractionmentioning
confidence: 99%
“…Recent studies focusing on soil-biochar-biota interactions in both terrestrial and aquatic ecosystems suggest potential impacts regarding the application of some biochars to soil on the activity and structure of edaphic and freshwater biological communities (due to leaching and potential transport of biochar particles into watercourse), their trophic relationships, and the processes they mediate. The extent and pattern of biological responses and/or observed toxicity can be assigned to bioavailable biochar fractions and appear to depend mainly on the target species and exposure scenarios, as well as on biochar physico-chemical properties and application rates (Busch et al 2012;Oleszczuk et al 2013;Smith et al 2012;Bastos et al 2014;Marks et al 2014;Domene et al 2015;Jaiswal et al 2015). A number of different mechanisms may play a role in determining biological responses to biochar amendment.…”
Section: Soil Biodiversity and Ecotoxicologymentioning
confidence: 99%